The Formation Of Intercultural Competence Among The Students In The Process Teaching English - Rifovich Fahrutdinov, Rifat (2017)
In the international level for modern journalist a linguistic and a cultural component have become increasingly important. In addition to knowledge in the professional field, future teacher needs to possess cultural, sociocultural knowledge and skills of intercultural communication.  Nowadays this problem is widely discussed due to the active growth of theoretical and practical interest in issues of intercultural communication. The introduction of a two-level education system (bachelor's and master's degrees) in Russia entails a considerable number of changes, including creating courses of a foreign language. These projects must be assembled as per the new government state measures the fundamental request of which is to build the level of intercultural skill of understudies during the time spent educating an outside dialect at a college.